Substrate-specific binding of 8-oxoguanine DNA glycosylase 1 (OGG1) reprograms mucosal adaptations to chronic airway injury - Pan, Lang; Vlahopoulos, Spiros; Tanner, Lloyd; Bergwik, Jesper; Bacsi, Attila; Radak, Zsolt; Egesten, Arne; Ba, Xueqing; Brasier, Allan R.; Boldogh, Istvan (Frontiers in Immunology, 2023)
Recent advances have uncovered the non-random distribution of 7, 8-dihydro-8-oxoguanine (8-oxoGua) induced by reactive oxygen species, which is believed to have epigenetic effects. Its cognate repair protein, 8-oxoguanine DNA glycosylase 1 (OGG1), reads oxidative substrates and participates in transcriptional initiation. When redox signaling is activated in small airway epithelial cells, the DNA repair function of OGG1 is repurposed to transmit acute inflammatory signals accompanied by cell state transitions and modification of the extracellular matrix. Epithelial-mesenchymal and epithelial-immune interactions act cooperatively to establish a local niche that instructs the mucosal immune landscape. If the transitional cell state governed by OGG1 remains responsive to inflammatory mediators instead of differentiation, the collateral damage provides positive feedback to inflammation, ascribing inflammatory remodeling to one of the drivers in chronic pathologies. In this review, we discuss the substrate-specific read through OGG1 has evolved in regulating the innate immune response, controlling adaptations of the airway to environmental and inflammatory injury, with a focus on the reader function of OGG1 in initiation and progression of epithelial to mesenchymal transitions in chronic pulmonary disease.